Two‐generation reproduction and limited teratology studies of ethanamizuril fed to rats. Issue 8 (2nd April 2020) - Zhao, Juan; Wang, Mi; Wang, Xiaoyang; Fei, Chenzhong; Xue, Feiqun; Zhang, Lifang; Wang, Zhaoxiong; Zhang, Keyu
Abstract: Ethanamizuril, a new anticoccidial agent that belongs to triazine derivatives, has a broad and good anticoccidial activity. To evaluate the reproductive toxicity and teratogenic potential of ethanamizuril, different concentrations of ethanamizuril were administered to Sprague–Dawley rats by feeding diets containing 0, 2, 8, and 30 ppm, respectively. Each group consisting of 30 males and 30 females (F0) was treated with different concentrations of ethanamizuril through a 13‐week period before mating and during mating, gestation, parturition and lactation. In the 30 ppm dose group, pup body weight on days 7 and 21 in F1 offspring and day 21 in the F2a offspring were significantly decreased. A limited teratogenicity study was performed in combination with the F1 generation of a two‐generation reproduction study. F1 offspring of the reproduction study were mated after weaning of the F2a offspring. Pregnant female rats were subjected to cesarean section on gestational day 20 for teratogenic examination. No obvious body weights, fetal body lengths, tail lengths, litter weights, number of viable fetuses, external, skeletal, or visceral malformations in fetuses were noted in any groups in the teratogenic test, but ethanamizuril could be passed on to offspring through lactation.